Dynamics in the circular restricted three body problem with perturbations - Abduljabar Ansari, Abdullah; Alam, Mehtab (International Journal of Advanced Astronomy, 2017)
This paper presents the dynamics in the restricted problem with perturbations i.e. the circular restricted three body problem by considering one of the primaries as oblate and other one having the solar radiation pressure and all the masses are variable (primaries and infinitesimal body). For finding the autonomized equations of motion, we have used the Meshcherskii transformation. We have drawn the libration points, the time series, the zero velocity curves and Poincare surface of sections for the different values of the oblateness and solar radiation pressure. Finally, we have examined the stability and found that all the libration points are unstable.